A Novel Technique for Bedside Anorectal Manometry in Humans - Bharucha, Adil E. (Neurogastroenterol Motil, 2015)
BACKGROUND: Currently, anorectal manometry (ARM), which is used to diagnose defecatory disorders and identify anal weakness in fecal incontinence (FI) is generally conducted in specialized laboratories. Our aims were to compare anorectal functions measured with high resolution manometry (HRM) and a novel portable manometry device. METHODS: Anal pressures at rest, during squeeze, and simulated evacuation, and rectal sensation were evaluated with portable and HRM in 20 healthy women, 19 women with constipation and 11 with FI. The relationship between anal pressures measured with portable and HRM was assessed by the concordance correlation coefficient [CCC], Bland Altman test, and paired t tests. KEY RESULTS: Anal pressures at rest [CCC 0.45; 95% CI 0.29, 0.58] and during squeeze [CCC 0.60; 95% CI 0.46, 0.72] measured with portable and HRM were correlated and inversely associated with the risk of FI. During simulated evacuation, the CCC for rectal pressure [0.62; 95% CI 0.43, 0.76] was greater than that for anal pressure [CCC 0.22; 95% CI 0.04, 0.39] and the rectoanal gradient [CCC 0.22; 95% CI 0.02, 0.41]. Rectal sensory thresholds for first sensation, the desire to defecate, and urgency measured by portable and HRM were also significantly correlated between techniques. For several parameters, differences between portable and HRM were statistically significant and the Bland Altman test was positive. CONCLUSIONS & INFERENCES: Anorectal pressures and rectal sensation can be conveniently measured by portable manometry and are significantly correlated with high resolution manometry.